Brahma and Ganesha - 70 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in [Four-headed Brahma is shown riding a swan, his mount. Ganesha is shown riding his mount, a mouse.